1997
DOI: 10.2118/35491-pa
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Review of the Use of Pseudorelative Permeabilities for Upscaling

Abstract: Summary The properties and limitations of different dynamic pseudorelative permeability methods are summarized. Severe difficulties common to all methods are discussed: choosing the number and locations of the coarse-grid rock types, defining the simulations from which the pseudos are generated, and the dependence of the pseudos on well rates and positions. It is concluded that, in practice, pseudos cannot be used reliably to scale up from a "fine-grid" geological model to a "coarse-grid" flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
135
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 238 publications
(143 citation statements)
references
References 16 publications
0
135
0
Order By: Relevance
“…This, in turn, can lead to a lack of robustness in the coarse-scale description. See Christie [1996] and Barker and Thibeau [1997] for further discussion of the overall approach. Recent work has demonstrated that the calculation of pseudo relative permeabilities using local boundary conditions based on effective medium theory can lead to significantly improved coarse-scale results [Wallstrom et al, 2000].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This, in turn, can lead to a lack of robustness in the coarse-scale description. See Christie [1996] and Barker and Thibeau [1997] for further discussion of the overall approach. Recent work has demonstrated that the calculation of pseudo relative permeabilities using local boundary conditions based on effective medium theory can lead to significantly improved coarse-scale results [Wallstrom et al, 2000].…”
Section: Methodsmentioning
confidence: 99%
“…Most such methods either attempt to minimize, and then neglect, subgrid effects [Durlofsky et al, 1996 or require the a priori estimate of the global flow field from which upscaled (or pseudo) flux functions are computed [Christie, 1996;Barker and Thibeau, 1997]. The present method does model subgrid effects, but it does not require a priori estimates of the global flow field.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed the scale dependency and methods for upscaling of P c -S w , K r -S w and s-S w relationships had been the subjects of intense study in the literature [7,[51][52][53][54][55][56]. Barker and Thibeau [51] and Renard and De Marsily [54] suggested that the constitutive relationship should be used at the same scale as that of a predictive model but the practicality would only be attained with upscaling. In this regard, Gasda and Celia [52] proposed correction for the coarse grid simulation so that it could match better with the fine grid simulations.…”
Section: Introductionmentioning
confidence: 99%
“…In general, all dynamic pseudofunctions, produced at large scales, where viscous forces become important, depend on boundary conditions and the underlying gridding properties. They are only correct for the specific grid and flow conditions used to derive them (Barker and Thibeau 1997;Barker and Dupouy 1999).…”
Section: Importance Of Upscalingmentioning
confidence: 99%